Social Dimensions of Autonomy in Language Learning
XI, 277 p.
Keywords: This book examines how autonomy in language learning is fostered and constrained in social settings through interaction with others and various contextual features. With theoretical grounding, the authors discuss the implications for practice in classrooms, distance education, self-access centres, as well as virtual and social learning spaces.